Sikap Toleransi Beragama Wanita Bercadar - Chandra, Muhammad Riyadi; Makrufi, Anisa Dwi (Fakultas Tarbiyah dan Ilmu Keguruan (FTIK) UIN Sayyid Ali Rahmatullah Tulungagung, 2024)
This study explores the attitude of religious tolerance among veiled women in social interaction and interfaith relations. Using a descriptive qualitative approach, data were collected using in-depth interviews with 10 veiled female informants living in a multireligious environment. Data analysis used a thematic approach to identify patterns of their experiences and perceptions related to tolerance. The results showed that most veiled women actively participated in social activities and were open to building interfaith discussions. They showed a high tolerance attitude, even though they often experienced societal stereotypes and discrimination. This tolerance stems from their desire to understand other people's perspectives and convey their values. This study emphasizes respecting differences to create harmony in a multicultural society. These findings provide in-depth insight into how religious identity can influence attitudes toward interfaith tolerance among certain groups.